Optimal design of an oil pipeline with a large-slope section. Issue 9 (2nd September 2019) - Wang, Bohong; Yuan, Meng; Yan, Yamin; Yang, Ke; Zhang, Haoran; Liang, Yongtu
ABSTRACT: One of the important issues in the operation of a long-distance oil pipeline in a large-slope area is pressure control, especially for the section after the turning point. In this study, a method to optimally design an oil pipeline with a large-slope section is proposed. The method is based on a stochastic mixed-integer linear programming model with minimal total cost as the objective function to determine the size of the pipeline, the location, the operational plan of pump stations and the location of pressure reduction stations. Hydraulic calculations and different types of oil product are considered. The uncertainty in flow rates of the pipeline is studied by the proposed stochastic programming approach. This method is applied to a real case of designing an oil product pipeline in a large-slope area.